Factors for non-acceptance of contraceptive methods amongst married women of reproductive age group in rural Patna - Shree, Vijay; Prasad, R. R.; Kumar, Sanjay; Sinha, Setu; Choudhary, Sanjay Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Population explosion has been India’s major problem since independence. It is a major obstacle to the overall progress of the nation. Adoption of family planning methods is one of the best solutions to tackle this problem. The present study was planned to determine the factors for non-acceptance of different contraceptive methods among married women of reproductive age group in rural areas of Patna. Methods: Study design: a community based cross sectional study. Study population: married women of reproductive age group (15-45 years). Study period: January 2012- July 2013. Study area: field practice area of PHC Sampatchak, Patna. Sample size: 705 using formula n =4p* q/d2. Study tool: pre tested semi-structured proforma. Collected data was analysed using latest version of SPSS. Results: 705 married women of reproductive age group were surveyed and it was found that out of 705 women only 230 (32.65%) were using contraceptive methods. Amongst the users 70.87% were using permanent method of contraception and that too female sterilization. Of the temporary method users (29.13%) 2.60% were using condom, 15.21% were using OCP (oral contraceptive pills) and 11.30% were using IUCD (Intra Uterine Contraceptive Device). Choice of contraceptive method was mostly OCP (71.4%) when duration of marriage was <5 years. Greater the duration of married life more was the acceptance of Tubectomy. The main reasons for non-acceptance of contraceptives method was desire for child (31.17%) followed by fear of side effects (21.05%). Want of male child and opposition by husband accounted for 8.45% &12% respectively. Conclusions: There is tremendous need to increase use of temporary contraceptives for spacing after one or two children. Male involvement in RCH care is essential. It is important to increase their participation as husbands often influence their wife’s decision regarding reproductive health.